Factors Affecting Stone-freeness in the Initial Session of RIRS in Childhood Kidney Stones - Onur Kaygısız; Yavuz Mert Aydın; Levent Turan; Burhan Coşkun (Journal of Urological Surgery, 2024)

(untitled)
Objective: To determine, the factors affecting stone-freeness in children after one session of retrograde intrarenal surgery (RIRS). Materials and Methods: The data of 102 children who applied RIRS in our clinic between February 2012-January 2022 were retrospectively evaluated. Eleven children were excluded. Ninety-one children were divided into two groups according to stone-free status in the first session. Factors affecting stone freeness were analyzed with univariate and multivariate analyses. The stone-kidney index was calculated using the stone size/kidney long muscle formula, and receiver operating characteristic (ROC) analysis was performed to determine the cut-off point of the presence of residue stone. Results: Forty-seven (51.6%) children were girls. The median age, stone size, and stone-kidney index were 7 (1-17), 11 mm (4-30), and 1.4 (0.24-3.6), respectively. Stone-free status was achieved in 74 patients (group 1) and residual stones were present in 17 patients (group 2). There was a significant difference between the two groups in terms of stone localization, stone size, stone-kidney index, power of the laser device, and operation time. According to multivariate analysis, multiple calyces’ stones [p=0.015, odds ratio (OR): 6.37] and stone size ≥2 cm (p=0.006, OR: 16.96) were factors that predicted residual stones. ROC analysis showed that the stone-kidney index at values above 1.96 was significantly associated with an increased risk of residual stone. Conclusion: Stone size ≥2 cm, and multiple calyx stones were risk factors for residual stones after one session of RIRS in children. Stone-kidney index values higher than 1.96 are associated with lower stone-free rates.